Evaluation of Entrepreneurship Learning Program of Electronic Faculty Of Engineering State University of Padang - Iffah Rojiyyah; Indrati K; Ambiyar Ambiyar (Postgraduate School, Universitas Negeri Padang, 2020)
This study aimed to evaluate entrepreneurial learning programs in electronics engineering department at Padang State University engineering faculty in terms of components of context, input, process and product. This study is an evaluation technique using a combination of data analysis (Mixed Method), starting with the use of quantitative methods followed by a qualitative method. Quantitative data was collected using a questionnairE, while that for qualitative data obtained from interviews between investigators and informants were selected. All data obtained will be analyzed by sequential explanatory design. These results indicate that the results of the evaluation in the context of components, inputs and processes that are in good enough category of products while the components are in good category.